Sub-wavelength structures and applications - Xu, Zhengji (2016)
Electromagnetic (EM) wave is currently a major research topic in the modern physics. To quantitatively describe the EM wave, the frequency and wavelength are the two critical parameters used. The frequency is in the time scale, representing the energy of EM wave; while wavelength (or wave number) is in the spatial scale, representing the momentum of the EM wave. Subwavelength optics is based on the light properties and behaviors of subwavelength scaled optical devices. In the visible and near infrared ranges, tens to hundreds nanometers (less than one quarter of the wavelength) subwavelength structures are meaningful to the optical manipulations and extraordinary properties controlling.